Sew eco-friendly : 25 reusable projects for sustainable sewing - Shore, Debbie (Writer on sewing) (Search Press Limited, 2021)
Sew 25 stylish, reusable projects to help reduce waste. Sew more, waste less. It's never been more important to be mindful of what we consume. This book will help you to make 25 small but meaningful life swaps to help reduce waste and live more sustainably. Replace disposable face wipes with skin-friendly, washable pads; make beeswax fabric wraps so that you never have to buy single-use plastic food wrap again; make a sturdy shopping tote to replace plastic bags; trade in gift wrap and tape for stylish fabric wraps and gift bags. Packed with all the easy-to-follow instructions and friendly sewing tips you expect from Debbie Shore, this book also contains hints and tips for face scrubs, bath salts and more to use with your new projects, or to make a perfect eco-friendly gift. Vegan alternatives are suggested where possible.